1979
DOI: 10.21236/ada067957
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric Techniques and Data Evaluation Methods for the UTIAS 10 cm x 18 cm Hypervelocity Shock Tube

Abstract: NOf j1 OI XRAN-MrlAL 10 r This tegbijqlrepot &W, b###4 'wiM &Od is 6111rov~ for puie"I" n nM.2 (7b). The UTIAS 10 cm x 18 cm Hypervelocity Shock.-Tube has) been used in recent years to study ionizing shock structures, flat-plate and side-wall boundary layers and nonstationary oblique shock-wave diffractions over compression corners. These phenomena were recorded using a 23-cm dia field of view Mach-Zehnder interferometer equipped with a giant-pulse dual-frequency ruby laser.In order to extract the maximum amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Stting t = 900 us gives the largest giant pulse with insignificant normal lasing; this is the setting used to take interferograms at this facility, in order to get one set of bright fringes with no "ghost" fringes (Ref. 19). For this study it was found that operating the Q-switch at an intermediate value of t produced a moderate-strangth giant pulse and several very-shortduration ngrmal-lasing pulses of usable energy.…”
Section: Pulsed Laser In Combined Modementioning
confidence: 94%
See 1 more Smart Citation
“…Stting t = 900 us gives the largest giant pulse with insignificant normal lasing; this is the setting used to take interferograms at this facility, in order to get one set of bright fringes with no "ghost" fringes (Ref. 19). For this study it was found that operating the Q-switch at an intermediate value of t produced a moderate-strangth giant pulse and several very-shortduration ngrmal-lasing pulses of usable energy.…”
Section: Pulsed Laser In Combined Modementioning
confidence: 94%
“…Up-dated alignment procedures are given in Ref. 19. A short description of the optical components involved will facilitate a discussion of the application of interferometry to the present study.…”
Section: Interferometer and Light Sourcementioning
confidence: 99%